Early visual field changes in patients with type 1 diabetes mellitus. Issue 6 (November 2020) - Ozates, Serdar; Simsek, Mert; Elgin, Ufuk; Keskin, Melikşah; Aycan, Zehra
Purpose: To assess the visual field sensitivity changes and investigate the association between visual field sensitivity and retinal nerve fiber layer thickness in patients with type 1 diabetes mellitus. Materials and methods: In this cross-sectional and observational study, 46 patients (22 males, 24 females) with type 1 diabetes mellitus and no diabetic retinopathy formed the diabetes mellitus group and 50 age-matched healthy subjects (32 males, 18 females) formed the control group. Retinal nerve fiber layer thickness, full-threshold standard automated perimetry, and short-wavelength automated perimetry were performed. Main outcomes were retinal nerve fiber layer thickness, mean deviation, pattern standard deviation, and short fluctuation. Results: Average retinal nerve fiber layer thickness was significantly thinner in the diabetes mellitus group (p < 0.001). The mean values of mean deviation and pattern standard deviation of the full-threshold standard automated perimetry did not differ between the groups (p = 0.179, p = 0.139, respectively). Mean short fluctuation was significantly greater in the diabetes mellitus group (p < 0.001). Both mean deviation and pattern standard deviation of the short-wavelength automated perimetry were significantly greater in the diabetes mellitus group (p < 0.001, p < 0.001, respectively). Pattern standard deviation of short-wavelength automated perimetry equal or higher than 1.57 dB had 91% sensitivity and 90% specificity (area under the curve = 0.969, p < 0.001) and short fluctuations of full-threshold standard automated perimetry equal or higher than 0.80 dB had 80% sensitivity and 76% specificity over detecting early retinal nerve fiber layer loss in patients with type 1 diabetes mellitus (area under the curve = 0.855, p < 0.001). Conclusion: This study showed that thinner retinal nerve fiber layer in patients with type 1 diabetes mellitus may be associated with abnormal retinal sensitivity to short-wavelength stimulations in short-wavelength automated perimetry; however, retinal sensitivity to white stimulus was similar to that in healthy subjects in full-threshold standard automated perimetry.